Nonlocal Symmetry, CRE Solvability, and Exact Interaction Solutions of the (2 + 1)-Dimensional Boussinesq Equation - Sixing Tao (Journal of Mathematics)
The (2 + 1)-dimensional Boussinesq equation is considered in this study. Nonlocal symmetries of the (2 + 1)-dimensional Boussinesq equation are obtained by means of the truncated Painlevé expansion. The consistent Riccati expansion (CRE) solvability of the Boussinesq equation is derived. Three special forms of soliton-cnoidal wave interaction solutions are discussed analytically and shown graphically.